The Relation Between Emotional Quotient and Self-Directed Learning Readiness of Students in Medical Faculty of Lampung University - Indah Anita Dewi; Dwita Oktaria; Betta Kurniawan (Medula, 2020)
Learning in medical faculties that use the method of problem-based learning (PBL) requires students to be able to study independently (SDL). Even though they have previously been exposed to SDL, students still do not have the readiness to study independently so that they cannot implement SDL well. Emotional quotient is the ability to manage the emotions of self and others. Students who have emotionally quotient will have good self-control so that there is greater potential for implementing independent learning. Emotional quotient is closely related to the readiness of individual independent learning. The higher the emotional quotient and self-directed learning readiness, the easier it is for individuals to be able to apply independent learning (SDL). This study aims to determine the relationship of emotional quotient with self-directed learning readiness of students in Medical Faculty of Lampung University. Data retrieval in this study using questionnaires tool that has been tested for validity and reliability. The sample uses a stratified random sampling technique from FK Unila medical students class of 2016, 2017, 2018 and 2019 as many as 255 samples. Univariate analysis showed most respondents have a high emotional quotient 83,9%, a moderate emotional quotient 16,1% and no respondents have a low emotional quotient. Respondents with a high self-directed learning readiness were 78,4 %, a moderate self-directed learning readiness 21,6% and no respondents have a low self-directed learning readiness. Bivariate analysis with chi-square test obtained p-value <0.05 and there is a significant relationship between emotional quotient and self-directed learning readiness of students in Medical Faculty of Lampung University.